Risk Factors for No-Reflow in Patients with ST-Elevation Myocardial Infarction Who Underwent Percutaneous Coronary Intervention: A Case-Control Study - Ying Yu; Yongquan Wu; Xianyi Wu; Jinwen Wang; Changhua Wang (Cardiology Research and Practice)
Background and Objectives. The no-reflow phenomenon is a poor prognosis for patients with ST-elevation myocardial infarction (STEMI) who underwent percutaneous coronary intervention (PCI). The purpose of this study was to identify the risk factors for no-reflow in patients with STEMI who underwent PCI. Methods. This case-control study retrospectively reviewed the medical data of patients treated with primary percutaneous coronary intervention within 12 h after STEMI onset between January 2010 and January 2013 at the Department of Cardiology of the Beijing Anzhen Hospital. Results. A total of 902 patients were included in the analysis. The basic characteristics between the reflow and no-reflow groups were similar, except for time-to-hospital admission, heart rate, plasma glucose, high-sensitivity C-reactive protein (hsCRP)/prealbumin (PAB), neutrophil count, intraaortic balloon pump, and aspiration thrombectomy. The multivariable analysis showed that hsCRP/PAB (OR = 1.003, 95% CI: 1.000–1.006, P=0.022), neutrophil count (OR = 1.085, 95% CI: 1.028–1.146, P=0.003), plasma glucose levels (OR = 1.086, 95% CI: 1.036–1.138, P=0.001), diabetes mellitus (OR = 0.596, 95% CI: 0.371–0.958, P=0.033), Killip classification >1 (OR = 2.002, 95% CI: 1.273–3.148, P=0.003), intraoperative intraaortic balloon pump (IABP) use (OR = 3.257, 95% CI: 1.954–5.428, P=0.001), and aspiration thrombectomy (OR = 3.412, 95% CI: 2.259–5.152, P=0.001) were independently associated with no-reflow. Conclusion. hsCRP/PAB, neutrophil count, plasma glucose levels, diabetes mellitus, Killip classification, intraoperative IABP use, and aspiration thrombectomy were independent risk factors for no-reflow in patients with STEMI.